History, objects, web. Collections and digital tools for digital public history - Caron, Mara (Umanistica Digitale, 2023)
Thanks to the spread of digital archives and collections, Public Historians have access to millions of digitized items, texts, and sounds reusable for historical communication on the web. This good practice encourages the production of narrations alternative to the official ones and acknowledges the educational value of material culture in the historiographical context. In this essay, we analyze some international and Italian digital collections to evaluate the query process and the reuse possibilities of the catalogued materials; furthermore, we describe some graphic and digital storytelling software to create multimedial, interactive content from digitized items. Eventually, we discuss three-dimensional digital objects, the frontier of digital collections: occasionally, they are employed in projects to produce immersive virtual realities. They are rich in potentiality but also puzzling; we can overcome difficulties by cooperating with expert computer scientists and adequately managing funds to create, store and make reusable three-dimensional digital items.